2022
DOI: 10.1101/2022.08.31.506028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling human endurance: Power laws vs critical power

Abstract: The power–duration relationship describes the time to exhaustion for exercise at different intensities. It is generally believed to be a "fundamental bioenergetic property of living systems" that this relationship is hyperbolic. Indeed, the hyperbolic (a.k.a. critical-power) model which formalises this belief is viewed as the "gold standard" for assessing exercise capacity, e.g. in cycling, running, rowing, and swimming. However, the hyperbolic model is now the focus of two heated debates in the literature bec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Gaesser et al (6) observed that the CP 3hyp reported the lowest CP value which did not differ with the work rate of the so-called ventilatory threshold for longterm exercise (i.e., the highest power output that could be maintained for 40 minutes without a rise in ventilation from the minute 20). This position the CP at work rates close to the 30-minute (CP 2hyp : 98 [4]%; CP 3hyp : 99 [4]%) and 60-minute (CP 2hyp : 103 [5]%; CP 3hyp : 104 [5]%) power output, which consequently enhance the accuracy of the estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaesser et al (6) observed that the CP 3hyp reported the lowest CP value which did not differ with the work rate of the so-called ventilatory threshold for longterm exercise (i.e., the highest power output that could be maintained for 40 minutes without a rise in ventilation from the minute 20). This position the CP at work rates close to the 30-minute (CP 2hyp : 98 [4]%; CP 3hyp : 99 [4]%) and 60-minute (CP 2hyp : 103 [5]%; CP 3hyp : 104 [5]%) power output, which consequently enhance the accuracy of the estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting long-distance running performance has been always of great interest to athletes and practitioners. It is well known that the capacity to sustain a work rate decreases with the increase of time, and different functions have been proposed to model it (5,14,20). On the one hand, the critical power (CP) models define the power-duration curve (PDC) along the severe-intensity domain.…”
Section: Introductionmentioning
confidence: 99%